INVESTIGATION OF MICROSTRUCTURE AND MECHANICAL PROPERTIES OF MAGNESIUM ALLOY COATED WITH INCONEL 625/WC COMPOSITES BY HVOF METHOD - Somer, Medeni; Gurgenc, Turan; Ilkilic, Cumali; Macit, Cevher Kursat (World Scientific Publ Co Pte Ltd, 2023)
In this study, Inconel 625 (IN625) alloy and tungsten carbide (WC) with additive ratios of 10%, 30% and 50% by weight were coated on the magnesium alloy surface. The coating process was carried out with the High Speed Oxy-Fuel Spray (HVOF) technique. Microstructure characterizations were performed by profilometry, optical microscope (OM), scanning electron microscope (SEM), energy distribution X-ray spectroscopy (EDS) and X-ray diffraction (XRD) analysis. Microhardness measurements and wear tests were also used to determine mechanical properties. Dry sliding wear tests were carried out at loads of 2, 6 and 10 N and at a sliding distance of 150 m. It has been observed that powder mixtures with different additive ratios form different microstructures. It was observed that the Surface Centric Cubic Structure (FCC) gamma (gamma) matrix and WC carbide as well as W2C, W6C2.54, M6C and M23C6 carbides were formed on the obtained coating layers. Depending on the increase in WC additive ratio, the surface roughness values increased. The microhardness values in the coating layers varied between 392 and 508 HV0.1 WC additive to Inconel 625 improved its hardness and wear resistance. While 0.64, 0.97 and 1.19 mg weight loss was measured for 2, 6 and 10 N in the pure AZ91 sample, these values were 0.12, 0.2 and 0.31 mg in the IN625WC-50 sample measured. The coating with the highest hardness and wear resistance was obtained with a high WC ratio.
Keywords: Surface coating; magnesium alloy; Inconel 625 alloy; tungsten carbide; wear